(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Establishment of identity is of cardinal importance in any forensic investigation. Lip Prints, if left behind, can be used to confirm if a particular person was present at the crime scene or not. Failures in establishing the identity by existing prevalent and accurate methods like fingerprint analysis, warrants the use of other methods for the same. Study of types of lip prints, its distribution and its association with ABO and Rh Blood Groups can be helpful in establishing the identity of the perpetrators. By assessing this, the presence or absence of an individual at a crime scene can be ascertained. The study group included 300 adult participants each of male and female sex. Each individual’s lip print pattern & ABO Blood groups were documented. Based on Suzuki & Tsuchihashi’s classification, lip prints were categorised. The data collected was tabulated & analysed statistically. The study revealed that, Type II lip print & B Positive blood group were predominant among sexes was Type II. Type II and III lip prints were predominant among A, B and O Rh-Positive blood groups. Type II followed by III and Type III followed by IV were the predominant patterns in Rh-Positive and Rh-Negative blood groups respectively. Statistical Analysis revealed that the most common Blood Group among Vertical lip print pattern population was O-Positive. The B-Positive blood group was the most prevalent among all the other patterns. Results of the study showed that lip print patterns bear an association with ABO blood groups and Rh type.